Sudden and Persistent Bradycardia: An Unexpected Indicator of Pin-Site Extradural Hematoma in a Pediatric Patient - Nandi, Roneeta; Redhu, Shruti; Patir, Rana; Dash, Hari Hara (Journal of Neuroanaesthesiology and Critical Care, 2018)
Depressed skull fracture and extradural hematoma are infrequent complications of skull pin fixation in children undergoing craniotomy. Neurosurgeons are often alerted about these complications by intraoperative brain swelling or postoperative neurological deterioration. We describe the development of pin-site extradural hematoma in a child on whom Mayfield skull clamp was applied during posterior fossa tumor excision. Sudden and persistent bradycardia observed by the anesthesiologist served as the sole warning sign. Such an on-table indicator of pin-site extradural hematoma has not been described earlier. The anesthesiologist must maintain vigilance and effective communication with surgical colleagues to ensure early detection and timely management of these pin-site complications.
Keywords: bradycardia; cranial fixation; depressed skull fracture; extradural hematoma; pediatric; pin-site complications; posterior fossa